Impacts of large-scale circulation patterns on the temperature extremes in the cold regions of China with global warming - Dong, Yiyang; Zhai, Jiaqi; Zhao, Yong; Liu, Zhiwu; Yang, Qin; Jiang, Shan; Lv, Zhenyu; Yan, Dianyi; Liu, Kuan; Ding, Zhiyong (Frontiers in Earth Science, 2023)
The cold regions of China (CRC) are important and vulnerable freshwater recharge areas on land, and any changes in them are related to the survival of millions of people in East Asia. However, for nearly half a century, in cold regions, the extreme temperature response to global warming is still poorly understood. In this study, we systematically studied the temperature extreme changes in cold regions of China since 1961 and discussed the possible circulation factors in detail. The results showed that 1) the warming magnitudes in cold nights and warm nights are greater than those in cold days and warm days, and decreases in cold nights and cold days and increases in warm days and warm nights appeared in almost all of cold regions of China. Most of the temperature indices displayed the largest magnitudes of warming in winter. 2) Spatially, for most of the temperature extremes, the stations located at Qinghai–Tibet Plateau (TPC) and Northwest China (NWC) showed a larger warming trend than that shown by the station at Northeast China (NEC). 3) The responses of temperature extremes at different cold regions to each circulation index are variable. Atlantic Multidecadal Oscillation (AMO) has a significant relationship with almost all the indices in cold regions of China. Almost all the temperature extremes of TPC and NWC showed closely relationship with the North Atlantic Oscillation (NAO), especially for diurnal temperature range (DTR), daily maximum temperature, and the cold extremes. Multivariate ENSO Index (MEI) is significantly related to most the temperature indices of Northwest China and Northeast China. However, MEI has a significant impact on only TPC’s diurnal temperature range and warmest night (TNx). 4) Atlantic Multidecadal Oscillation displayed significant relationships with most the temperature extremes in every season in cold regions of China. However, the summer and winter MEI and the summer and winter North Atlantic Oscillation showed significant impacts on only diurnal temperature range, daily minimum temperatures (TNm), and TNx.